2020
DOI: 10.1183/23120541.00318-2019
|View full text |Cite
|
Sign up to set email alerts
|

Ivacaftor decreases monocyte sensitivity to interferon-γ in people with cystic fibrosis

Abstract: Management of cystic fibrosis has been revolutionised by the introduction of cystic fibrosis transmembrane conductance regulator (CFTR) modulators. These compounds treat the underlying molecular basis of the disease by increasing activity of defective CFTR channels, which improves many clinical parameters and enhances patient quality of life [1]. Next-generation modulators, also known as triple combination therapy, promise to be highly efficacious in up to 90% of patients [2] and will likely dramatically chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Sweat chloride changed from 77.5 (+/-4) mmol/l to 52.1 (+/-5.61) after 7 days of treatment (p<0.001, paired t-test) confirming a pharmacodynamic response to therapy, FEV 1 also improved at 7 days as detailed in a contemporaneous study in the same patient cohort (10).…”
Section: Patient Demographicssupporting
confidence: 60%
“…Sweat chloride changed from 77.5 (+/-4) mmol/l to 52.1 (+/-5.61) after 7 days of treatment (p<0.001, paired t-test) confirming a pharmacodynamic response to therapy, FEV 1 also improved at 7 days as detailed in a contemporaneous study in the same patient cohort (10).…”
Section: Patient Demographicssupporting
confidence: 60%
“…ATF3 (Activating Transcription Factor 3, FDR = 3.11 × 10 −10 ) binds CRE elements in DNA and represses transcription, and has been shown to negatively regulate pro-inflammatory cytokine expression in macrophages ( Rosenberger et al., 2008 ; Labzin et al., 2015 ). We recently showed that monocytes from the same cohort described here exhibit a decrease in ex vivo responsiveness to IFNγ after subjects have received ivacaftor for 7 days ( Hisert et al., 2020 ). An increased expression of genes that deactivate or dampen inflammatory signaling could partly explain why transcriptome data predicted that these monocytes have a more inflammatory phenotype while the same cells, when stimulated ex vivo , exhibited decreased IFNγ responses.…”
Section: Discussionmentioning
confidence: 71%
“…In order to characterize the inflammatory phenotype of in vivo blood monocytes in people with CF, and to determine how cellular phenotypes change in response to CFTR modulator therapy, we have used unbiased “omics” methods to identify changes in freshly isolated peripheral blood monocytes following initiation of ivacaftor in people with susceptible CFTR mutations. Previously we identified changes in the monocyte plasma-membrane associated proteome in subjects with CFTR-G551D mutations that suggested that CFTR modulator therapy causes a decrease in monocyte IFN γ responses ( Hisert et al., 2016 ), a hypothesis that we have since confirmed ( Hisert et al., 2020 ). Here we describe how restoration of CFTR activity by ivacaftor acutely changes the peripheral blood monocyte transcriptome and plasma chemokines in a cohort of adults with CF and the CFTR mutation R117H.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…The effects of CFTR modulators on inflammation in general, and the impact they have on intrinsic defects of the innate immune response in PWCF, are thus far under-characterised. The effects of CFTR modulators in clinical trials have focused on pulmonary function, PEx, and quality of life measures, which are important clinical outcomes [ 6 , 7 , 8 , 9 , 10 , 11 ] and are also required for regulatory approval [ 116 ]. Furthermore, existing published research is mainly limited to the effects of the potentiator, ivacaftor (IVA), with little data relating to the other modulator therapies available as yet.…”
Section: Effects Of Cftr Modulators On Inflammationmentioning
confidence: 99%